Prognostic Value of CD9 in Solid Tumor: A Systematic Review and Meta-Analysis - Zeng, Ping; Si, Meng; Sun, Rui-xia; Cheng, Xu; Li, Xiao-yang; Chen, Min-bin (Frontiers in Oncology, 2021)
Numerous clinical studies investigated how low expression of CD9 predicts poor prognosis of solid tumor. However, the results were inconclusive. This present meta-analysis was therefore performed to determine the prognostic value of CD9 expression in solid tumors. In this meta-analysis, 25 studies involving 5,555 participants were included; the result showed strong significant associations between declined expression of CD9 and all endpoints: overall survival (OS) (hazard ratio (HR) = 1.88, 95% CI = 1.45–2.43, p < 0.000) and time to progression (TTP) (HR = 2.0, 95% CI = 1.38–2.88, p < 0.000). The subgroup analysis was also performed, which revealed that the associations between CD9 downregulated expression related to poor OS in lung cancer and head and neck cancer. Also, low expression of CD9 was significantly connected with poor TTP in patients with head and neck cancer. The adverse prognostic impact of decreased expression of CD9 was observed in patients of different ethnicities. In conclusion, these results showed that declined expression of CD9 was associated with poor survival in human solid tumors. CD9 may be a valuable prognostic predictive biomarker and a potential therapeutic target in human solid tumors.